MESS Scale for Combat Limb Injury: Amputation or Salvage? - Liabakh, A.P.; Derkach, R.V.; Kostogryz, O.A. (TERRA ORTHOPAEDICA, 2022)
Summary. Combat injury of the limbs is characterized by multilevel open combined tissue damages, the severity of which in some cases makes it impossible the salvage tactics. Objective: based on the analysis of literature, to investigate the possibility of using MESS (the mangled extremity severity score - assessment of the severity of a broken limb) when establishing indications for early amputation of a severely injured limb due to a combat trauma. Materials and Methods. A literature search was conducted on the PubMed database according to the established criteria. Data were taken from the selected sources: the number of amputation/save cases and the weighted average MESS amputation/save value. A weighted average MESS with a 95% confidence interval (CI) and a coefficient of variation were calculated. Results. A total of 189 sources according to the established criteria were identified for the period 1990-2021, in which MESS was applied; 7 sources were selected for analysis. The generalizing value (weighted average) for MESS for amputations was 7.3; 95% CI (6.27-8.33); the coefficient of variation was 4.1. While preserving the limb, the calculations showed a MESS value of 4.9; 95% CI (4.49-5.31); the coefficient of variation was 8.4. Conclusions. The use of the MESS makes it possible to assess the condition of the injured limb; the value of 7 or above is a reliable predictor for amputation.